Tail autotomy effects on the escape behavior of the lizard Gonatodes albogularis (Squamata: Sphaerodactylidae), from Córdoba, Colombia - Domínguez López, Moisés E. (2015)
Background: Caudal autotomy appears to be an adaptation strategy to reduce the risk of being preyed upon. In an encounter with a predator, the prey must reduce the risk of being preyed upon, and one of the strategies that has exerted a strong pressure on selection has been tail loss. In lizards, it has been demonstrated that tail loss reduces the probability of survival in the event of a second attack; therefore, they must resort to new escape strategies to reduce the risk of falling prey. In order to evaluate the effect of tail loss on the escape behavior of Gonatodes albogularis in natural conditions, we took samples from a forest interior population. We expected that individuals that had not lost their tails would allow the predator to get closer than those that had lost it. For each sample, we recorded the following: (1) escape behavior, measured through three distances (e.g., approach distance, escape distance, and final distance); (2) distance to shelter; and (3) length of tail. We included only males in the study since we did not record any females without a tail and far fewer with a regenerated tail. Results: We found that tail loss does have an effect on the escape behavior of G. albogularis. Males that have their tails intact allow the predator to come closer, and we found a negative correlation between the approach distance and the length of the tail. Conclusion: Our results support the escape behavior theory, in which G. albogularis males drop their tails when the risk of predation is much higher than the cost of fleeing.